Token Reinforcement, Cognitive Behavioural Therapy, Degree of Disability and Managing Aggressive Behaviour Among Pupils With Intellectual Disability - Udeme Samuel Jacob; Kehinde Rechael Adegboye; Jace Pillay (Pedagogical Discourse, 2022)
Aggressive behaviour has a significant negative effect on learning and academic performance. This study aimed to establish the main effect of token reinforcement, cognitive behavioural therapy, and degree of disability on reducing aggression among pupils with intellectual disability. The study participants were 60 pupils (N = 60, N = 27 boys; N = 33 girls; mean age = 11.7) with intellectual disability who were purposively selected from three (3) special schools in the study location. The participants were divided into three treatment groups: token reinforcement, cognitive behavioural therapy, and control groups, with the degree of disability as the moderating factor. The token reinforcement and cognitive behavioural therapy groups met for thirty sessions over twelve weeks. Three experimental (two treatment and a control) groups were assessed using the Overt Aggression Scale, while the three treatment groups were assessed post-intervention using the Overt Aggression Scale. Data for aggressive behaviour performance were collected after the participants were screened for intellectual disability. An analysis of covariance and estimated means was used to examine the data. The results revealed a statistically significant difference between the pre-test and post-test results of the three (3) treatment groups. The degree of disability had significant main effect on level aggressive behaviour among pupils with intellectual disability. The interaction effect of treatment and degree of disability was significant on participants’ aggressive behaviour. Teachers and care givers should adopt token reinforcement and probably cognitive behavioural therapy in manage aggressive behaviour among pupils with intellectual disability.